Dampak Implementasi Program Pembelajaran Merdeka Belajar Kampus Merdeka (MBKM) di Universitas Almuslim - Misnawati Misnawati; Zuraini Zuraini (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This study aims to determine the impact of the implementation of learning activity of Independent Learning Independent Campus (MBKM) program on the learning obtained by students at Almuslim University. Specifically, the research objectives were to identify the impact of the implementation of MBKM, to investigate the students’ perceptions and attitudes towards MBKM program. The research of methodology was a qualitative descriptive research. The data of techniques collection were interview and survey, while the data analysis technique used was descriptive analytical by applying formative evaluation research. This research seeks to figure the quality improvement in students’ learning and to find out what actually happened in the natural context when the program was still running, with the goal to boost the quality of the MBKM program in the future. The data provided through questionnaires and interview, data analysis techniques started from data collection which was then analyzed using descriptive analysis. The research results shown that the impact of the implementation of MBKM can improve the soft skills and hard skills of the students after participating in the Independent Learning Independent Campus program. Keywords: Impact; Implementation; Learning Program; Independent Learning